Pedagogical Conditions for the Realization of Professional Training of Future Translators on the Basis of the Integrative Approach - Savka, Iryna (Pedagogical Discourse, 2020)
The article substantiates the pedagogical conditions for the implementation of professional training of future translators on the basis of an integrative approach. It is proved that for the professional training of future translators it is necessary to focus on professional integration of knowledge and skills; ensure the integration of professional training of translation specialists; implementation of integrated content, methods and forms of implementation of the integrative approach in training for the students of the specialty "Philology). It is noted that one of the tasks of improving the professional training of professional translators is the formation future translators’ professionally-oriented lexical awareness. The professional skills of a translator are found to be flexible and successful in performing professional duties in non-standard, unusual, diverse situations. It is determined that one of the main functions of a translator’s professional activity is communicative. The article justifies the pedagogical conditions of professional training of future translators based on an integrative approach aimed to ensure internal professional integration of knowledge and skills of linguistic disciplines (general foreign language subsystem of the professional training for a future translator), the provision of external professional integration of the knowledge and skills of the professional foreign language training, the formation of an integrated training system of a future translator. The article shows the features of the integration of knowledge and skills for future translators such as the integration of knowledge and skills in foreign languages learning, which helps to optimize the theoretical and practical components of the future translators training; the doubled integration of knowledge and helps to update the content of the professional training; the provision of the constant updating of knowledge and skills of languages by the specialist in translation.